Electropolymerization mechanism in aqueous solution of the oxo-manganese complex biomimicking of the enzymatic center present on the photosystem II - Martin, C. S. [UNESP]; Teixeira, M. F S [UNESP] (The Electrochemical Society, 2012)
The [Mn4 IVO5(terpy)4(H 2O)2]6+ complex, show great potential for electrode modification by electropolymerization using cyclic voltammetry. The electropolymerization mechanism was based on the electronic transfer between dx2-y2 orbitals of the center metallic and pπ orbital of the ligand, which show great complexity of the system due to orbitals overlap present in octahedral complex of the metal-μ-oxo. The voltammetric behavior both in and after electropolymerization process were also discussed, where the best condition of electropolymerization was observed for low scan rate and 50 potential cycles. A study in ITO/glass electrode for better characterization of polymer was also performed. ©The Electrochemical Society.
Keywords: Bio-mimicking; Electrode modification; Electronic transfers; Octahedral complex; Photosystem II; Potential cycles; Scan rates; Voltammetric behaviors; Cyclic voltammetry; Manganese; Electropolymerization